Are litter decomposition and fire linked through plant species traits?. Issue 3 (11th September 2017) - Cornelissen, Johannes H. C.; Grootemaat, Saskia; Verheijen, Lieneke M.; Cornwell, William K.; van Bodegom, Peter M.; van der Wal, René; Aerts, Rien
Summary: Biological decomposition and wildfire are connected carbon release pathways for dead plant material: slower litter decomposition leads to fuel accumulation. Are decomposition and surface fires also connected through plant community composition, via the species' traits? Our central concept involves two axes of trait variation related to decomposition and fire. The 'plant economics spectrum' (PES) links biochemistry traits to the litter decomposability of different fine organs. The 'size and shape spectrum' (SSS) includes litter particle size and shape and their consequent effect on fuel bed structure, ventilation and flammability. Our literature synthesis revealed that PES‐driven decomposability is largely decoupled from predominantly SSS‐driven surface litter flammability across species; this finding needs empirical testing in various environmental settings. Under certain conditions, carbon release will be dominated by decomposition, while under other conditions litter fuel will accumulate and fire may dominate carbon release. Ecosystem‐level feedbacks between decomposition and fire, for example via litter amounts, litter decomposition stage, community‐level biotic interactions and altered environment, will influence the trait‐driven effects on decomposition and fire. Yet, our conceptual framework, explicitly comparing the effects of two plant trait spectra on litter decomposition vs fire, provides a promising new research direction for better understanding and predicting Earth surface carbon dynamics.   Contents     Summary 653 I. Introduction 654 II. Decomposition–fire interactions via traits in the plant economics spectrum (PES) 657 III. Fire–decomposition interactions via traits in the size and shape spectrum (SSS) 659 IV. Integrating decomposition–fire interactions: decoupling of PES and SSS effects? 661 V. From species to communities: are litter interactions for decomposition and fire behaviour connected? 662 VI. Feedbacks between community (trait) composition, decomposition and fire 663 VII. Conclusion 665   Acknowledgements 665   References 665